Assesing Digital Evidence Availability in Discord Phishing using ISO/IEC 27037 and Anti-Forensics Analysis - Yudhana, Anton; Rivai, Zulki Yanto; Riadi, Imam (International Journal of Advances in Data and Information Systems, 2026)
Phishing incidents on modern communication platforms pose significant challenges for digital forensics investigations, particularly regarding the availability and preservation of digital evidence. This research aims to evaluate the availability of digital evidence in Discord-based phishing cases by applying the ISO/IEC 27037 framework and interpreting the results from an anti-forensics perspective. This research uses a digital forensics case analysis approach on the victim’s mobile device by following the stages of identification, collection, acquisition, and preservation. The results show that of the five types of digital evidence identified, only 40% can be fully preserved, while 20% are partially preserved, and 40% cannot be preserved. The quantitative evaluation produced an average digital evidence availability score of 0.5, indicating that only half of the expected digital evidence could be retained even though the entire forensics procedure had been systematically applied. These findings confirm that the limitations in the availability of digital evidence are influenced not only by the investigation process but also by the technical characteristics of digital artifacts and the system mechanisms inherent to the Discord platform.